24-HOUR BLOOD PRESSURE MONITORING PARAMETERS AND THE NUMBER OF METABOLIC SYNDROME COMPONENTS - Yu. V. Zhernakova; I. E. Chazova; S. P. Olimpieva; V. V. Kilikovskyi (Российский кардиологический журнал, 2011)
Arterial hypertension (AH) is one of the most prevalent components of metabolic syndrome (MS). At the same time, AH is a major risk factor predicting the development and progression of cardiovascular disease. The available literature provides inconsistent evidence on the association between the number of present MS components, blood pressure (BP) levels, and disturbed circadian BP profile. This study demonstrated that a higher number of MS components is linked to a higher AH stage and higher mean levels of most circadian, daytime, and nighttime parameters of 24-hour BP monitoring. Moreover, there was a significant increase in the numbers of “non-dippers” (patients with inadequate nighttime BP reduction), which is associated with a higher risk of cardiovascular events.